2010
DOI: 10.1161/circresaha.109.208439
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Inhibits Neuronal Nitric Oxide Synthase Activation Through the ERK1/2-RSK Signaling Pathway to Modulate Central Control of Blood Pressure

Abstract: Rationale: Angiotensin (Ang) II exerts diverse physiological actions in both the peripheral and central neural systems. It was reported that the activity of Ang II is higher in the nucleus tractus solitarii (NTS) of spontaneously hypertensive rats (SHRs) and that angiotensin type-1 receptors are colocalized with NAD(P)H oxidase in the neurons of the NTS, resulting in the induction of local reactive oxygen species production by Ang II. However, the signaling mechanisms of Ang II that induce hypertension remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…28 In a previous study, we showed that angiotensin II induces superoxide generation, which impairs NO production in the NTS. 10 The depressor effect of NO in the NTS occurs through the inhibition of sympathetic nervous activity. 30 Our findings extend previous observations that central insulin resistance in the NTS might participate in a superoxide-dependent pathway via the impairment of NO production to produce hypertension of fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In a previous study, we showed that angiotensin II induces superoxide generation, which impairs NO production in the NTS. 10 The depressor effect of NO in the NTS occurs through the inhibition of sympathetic nervous activity. 30 Our findings extend previous observations that central insulin resistance in the NTS might participate in a superoxide-dependent pathway via the impairment of NO production to produce hypertension of fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NO has important modulatory functions in the NTS, including the modulation of arterial BP and sympathetic nerve activity. 10 In previous experiments, we demonstrated that insulin microinjected into the NTS induces a depressor effect and initiates an interaction between insulin and phosphatidylinositol 3-kinase Abstract-Recent clinical studies found that fructose intake leads to insulin resistance and hypertension. Fructose consumption promotes protein fructosylation and formation of superoxide.…”
mentioning
confidence: 99%
“…In particular, previous studies have demonstrated that several neuromodulators, including angiotensin II acting on AT 1 receptors, are involved in cardiovascular regulation within the NTS (Arnold et al, 2010;Cheng et al, 2010Cheng et al, , 2012Kasparov et al, 1998;Mosqueda-Garcia et al, 1990). Accordingly, high levels of ACE (Rogerson et al, 1995) and high densities of AT 1 receptors have been found at the level of the NTS in the rabbit (Aldred et al, 1993) as well as in many other mammals including humans (Paul et al, 2006;Premer et al, 2013;Wright and Harding, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…But recently, Wen et al [36] found nNOS increased after inhibition of Ang II downstream of AT 1 R or depletion of ROS in the NTS of SHR S which suggests nNOS might be one of the downstream targets of Ang II that is involved in NO production and that modulates blood pressure function in the NTS of SHRs. They also observed that ROS accumulation inhibited ERK1/2 activation in the NTS and induced hypertension.…”
Section: The Erk1/2-rsk-nnos Signaling Pathwaymentioning
confidence: 99%